PROBLEMATIKA GURU SEKOLAH DASAR DALAM PEMBELAJARAN MENULIS TEKS NARASI SELAMA PANDEMI COVID-19 - Faraditha Dwi Ramayani; Rahman2; Vismaia S. Damaianti (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article is derived from the problems that arose in learning to write narrative texts during the covid-19 pandemic. The study in this article aims to determine the obstacles faced by elementary school teachers when teaching and learning process to write narrative texts during the covid-19 pandemic. Furthermore, the method used was descriptive qualitative by giving questionnaires and conducting interviews. The subjects were 10 elementary school teachers in Bukit Batu, Bengkalis Riau. The results indicated that in general elementary school teachers were not ready to do online learning. Another obstacle that obstructed the learning process was the lack of teachers’ and students’ understanding regarding the use of distance learning applications. Nevertheless, government support that has helped to ease the burden by providing free quota subsidies to teachers and students and the availability of Wi-Fi in some areas did not maximize use for online learning process.